Building Evidence for Pre-school Policy Change in Bulgaria - Volen, Eugenia; de Laat, Joost (Frontiers in Public Health, 2021)
In September 2020, Bulgaria’s National Assembly (parliament) passed legal amendments aimed at increasing kindergarten participation for children aged 4-6 in Bulgaria, with poor children standing to benefit the most. For the first time, state budget funds were set aside to relieve parents of the costs of monthly attendance fees currently collected by full-day kindergartens. It builds on evidence generated from a large-scale randomized control trial (RCT) (2014-2018) across 236 poor communities, implemented by the Trust for Social Achievement (TSA) together with the World Bank and the Abdul Latif Jameel Poverty Action Lab. This paper describes how the RCT was used by TSA to advocate for removal of fees, and how much more evidence besides the RCT needed to be generated and support needed to be mobilized to influence policy action.